IMPLEMENTASI PELAYANAN INAPORTNET DI KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS 1 TANJUNG BALAI KARIMUN - Nurisa Nazira Putri, Nurisa Nazira Putri (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2022)
This journal discusses the implementation of the inaportnet service that is applied to the port authority and port office of Class 1 Tanjung Balai Karimun. This journal explains about inaportnet users who still have problems between shipping agents and the organizers, this study uses qualitative research using data collection and interviews, data collection using data reduction, and primary data sources and secondary data sources. From the results of this study, the presence of inaportnet can be an easy-to-use solution between shipping agents and the organizers. In order to improve services at the harbor office and port authority class 1 Tanjung Balai Karimun. Keywords: implementation, inaportnet and service